2016
DOI: 10.1093/ecco-jcc/jjw219
|View full text |Cite
|
Sign up to set email alerts
|

The Pathogenic Role of NLRP3 Inflammasome Activation in Inflammatory Bowel Diseases of Both Mice and Humans

Abstract: Abnormal activation of NLRP3 inflammasome plays a major pathogenic role in the development of chronic colitis in IL-10-/- mice and humans. Glyburide, an FDA-approved drug, may have great potential in the management of inflammatory bowel diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
106
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 109 publications
(112 citation statements)
references
References 46 publications
6
106
0
Order By: Relevance
“…Two other reports, both using IL-10 -/-mice but by different experimental approaches, provided consistent evidence supporting a pathogenic function of the NLRP3 inflammasome in IBD [3,9]: One report in 2014 showed that IL-1b was increased in IL-10 -/-mice and that an IL-1b receptor antagonist or caspase-1 inhibitors ameliorated colitis [9]. The other report published in 2017 using both IL-10 -/-mice and human mucosal explant culture demonstrated that chemically inhibiting the NLRP3 inflammasome potently suppressed the intestinal mucosal inflammation of both mice and humans [3]. The reason for the inconsistency is unknown.…”
Section: Nlrp3 Inflammasomes and Ibdsupporting
confidence: 54%
See 4 more Smart Citations
“…Two other reports, both using IL-10 -/-mice but by different experimental approaches, provided consistent evidence supporting a pathogenic function of the NLRP3 inflammasome in IBD [3,9]: One report in 2014 showed that IL-1b was increased in IL-10 -/-mice and that an IL-1b receptor antagonist or caspase-1 inhibitors ameliorated colitis [9]. The other report published in 2017 using both IL-10 -/-mice and human mucosal explant culture demonstrated that chemically inhibiting the NLRP3 inflammasome potently suppressed the intestinal mucosal inflammation of both mice and humans [3]. The reason for the inconsistency is unknown.…”
Section: Nlrp3 Inflammasomes and Ibdsupporting
confidence: 54%
“…Although human research is far more challenging to conduct than comparable experimental studies, it is the only means to assure the relevance of conclusions derived from data obtained in experimental models. A recent report in which the expression of the NLRP3 inflammasome by western blot analysis of the colonic mucosa from IBD patients and healthy controls reported that NLRP3, ASC, and IL-1b were all significantly elevated in the mucosae of CD patients, compared with those obtained from of UC and healthy controls, but did not reach statistical significance in UC vs healthy controls [3]. Moreover, inhibition of the NLRP3 inflammasome with glyburide effectively suppressed the release of major proinflammatory cytokines/ chemokines by cultured colonic mucosal explants obtained from Crohn's patients [3].…”
Section: Nlrp3 Inflammasomes and Ibdmentioning
confidence: 93%
See 3 more Smart Citations